2022
DOI: 10.32615/ps.2022.014
|View full text |Cite
|
Sign up to set email alerts
|

Response of upland cotton (Gossypium hirsutum L.) leaf chlorophyll content to high heat and low-soil water in the Arizona low desert

Abstract: The sustainable production of upland cotton, an economically important fiber crop, is threatened by changing environmental factors including high temperatures and low-soil water content. Both high heat and low-soil water can reduce net photosynthesis resulting in low fiber yields or poor fiber quality. Leaf chlorophyll content has a direct relationship with photosynthetic rate. Understanding how high heat and low-soil water affect chlorophyll content can identify opportunities for breeding improvement that wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The highest positive correlation was observed between net photosynthetic rate and total chlorophyll contents (r = 0.997**), while the highest negative correlation was seen between net photosynthetic rate and superoxide dismutase (r = -0.983**) (Table 4). Similar findings were reported by Majeed et al, 2024, Thompson et al, 2022and Lopez et al, 2003 who showed a significantly stronger association of morphological, physiological and biochemical traits with seed cotton yield and its quality under heat stress conditions. Therefore, these characters must be considered while selecting the parental material and subsequent generations to develop heat-tolerant, climatesmart cotton genotypes.…”
Section: Analysis Of Variance (Anova)supporting
confidence: 90%
“…The highest positive correlation was observed between net photosynthetic rate and total chlorophyll contents (r = 0.997**), while the highest negative correlation was seen between net photosynthetic rate and superoxide dismutase (r = -0.983**) (Table 4). Similar findings were reported by Majeed et al, 2024, Thompson et al, 2022and Lopez et al, 2003 who showed a significantly stronger association of morphological, physiological and biochemical traits with seed cotton yield and its quality under heat stress conditions. Therefore, these characters must be considered while selecting the parental material and subsequent generations to develop heat-tolerant, climatesmart cotton genotypes.…”
Section: Analysis Of Variance (Anova)supporting
confidence: 90%
“…Insufficient chlorophyll content leads to reduced photosynthetic rates, hampering the generation of organic matter and energy output, ultimately negatively impacting crop yields. Moreover, dynamic changes in chlorophyll content also serve as an indicator of plant age, as crops with strong yields tend to possess long-lasting green leaves [51,52]. Previous studies have indicated that the application of appropriate straw mulch to wheat can significantly enhance its chlorophyll content and photosynthetic rate [53].…”
Section: Effects Of Different Straw Returning Measures On Cotton's Ch...mentioning
confidence: 99%
“…The amalgamation of these findings offers a comprehensive perspective on how cotton plants effectively manage physiological disruptions triggered by salinity stress. Drawing on current research, it intricately outlines the response of plants to water scarcity, elucidating the adaptive mechanism of reduced stomatal conductance as a strategic effort to conserve water [87,88]. A noteworthy contribution of the chapter lies in its exploration of altered water potential under drought conditions.…”
Section: Physiological Changes In Response To Abiotic Stress In Cottonmentioning
confidence: 99%